Platelet-monocyte aggregates: molecular mediators of thromboinflammation - Rolling, Christina C.; Barrett, Tessa J.; Berger, Jeffrey S. (Frontiers in Cardiovascular Medicine, 2023)
Platelets, key facilitators of primary hemostasis and thrombosis, have emerged as crucial cellular mediators of innate immunity and inflammation. Exemplified by their ability to alter the phenotype and function of monocytes, activated platelets bind to circulating monocytes to form monocyte-platelet aggregates (MPA). The platelet-monocyte axis has emerged as a key mechanism connecting thrombosis and inflammation. MPA are elevated across the spectrum of inflammatory and autoimmune disorders, including cardiovascular disease, systemic lupus erythematosus (SLE), and COVID-19, and are positively associated with disease severity. These clinical disorders are all characterized by an increased risk of thromboembolic complications. Intriguingly, monocytes in contact with platelets become proinflammatory and procoagulant, highlighting that this interaction is a central element of thromboinflammation. Platelets interact and bind to monocytes by a variety of mechanisms, including attachment of platelets to monocytes via platelet P-selectin and monocyte PSGL1, the release of platelet granules containing chemokines and cytokines, and shedding of platelet-derived microvesicles. These interactions result in the upregulation of monocyte proinflammatory surface markers (e.g., CD40), migration (CD11b/CD18), and procoagulant tissue factor (TF), a principal initiator of coagulation. In addition, monocytes exposed to platelets secrete proinflammatory cytokines (TNF-α, MCP-1, IL-1β) and exhibit a proinflammatory transcriptome. Furthermore, platelets skew monocyte and macrophage differentiation towards a proatherosclerotic phenotype. Our review covers how platelets affect monocytes in inflammatory diseases, and we present recent findings on potential therapeutic strategies to target the platelet-monocyte proinflammatory axis in thromboinflammation.